A PRÁTICA DE PLANEJAMENTO ESTRATÉGICO EM PEQUENAS EMPRESAS. O CASO DE MICRO E PEQUENAS EMPRESAS DO SETOR MINERÁRIO NO NOROESTE DO ESTADO DO RIO DE JANEIRO - Figueiredo, Paulo Cezar Ramos (2014)
The purpose of this paper is of renewing the understanding of what is the strategic planning in small business enterprises and, insofar as possible, to allow a careful consideration about the need of understanding new and valid models when restructuring their strategy. Nevertheless, the importance of forecasting, and the establishment of programs and subsequent initiatives should be highlighted, in a way of ensuring their survival in such competitive market. This study includes a review of the literature focused on planning, strategy formulation, accomplishment, follow up and control of the strategic plan. The study provides a survey of the theoretical references related to the strategic planning, and correlation with the main components related with a company s management, designed to support its administrators in the process of determining the strategic purposes, their accomplishment and eventual revision, emphasizing the search for putting in a context the requirements and restrictions imposed to micro- and small-scale businesses. This research aims to assess the current stage of the participating companies, beginning with those with positive results correlated with the evidence they have been following a previous plan, in order to identify the extent of the adopted practices, using as guidelines the FNQ parameters and the conceptual models of the main theoretical frameworks. It is expected the research confirms, through case study, the existence of successful reduced models (by comparison with existing textbook models), considering the shortage of resources available for micro and small businesses, in relation to those accessible to medium- and large-sized enterprises, which are the source of most models mentioned in the literature.